The Influence Of Budget Participation, Information Asymetricity And Budget Emphasis On Budget Gap On Community Empowerment Offices And Villages Of West Sumatera Province - Febryandhie Ananda; Syamratul Ikhwan (Future Science, 2021)
Budgetary slack is a gap by managers or subordinates in participating to budget by giving budget estimates that do not fit the actual situation. The purpose of this study to determine the influence of budget participation, asymmetry of information and budget emphasis towards budgetary slack. The research was conducted at Department of community empowerment and the village west sumatera province. The respondents in this study are those of the budget as many 40 samples were collected for analysis by using total sampling method. Designs in this research is quantitative method. Methods of data analysis using multiple regression analysis by SPSS 25.0 software program. The results shows that budget participation give positive effect and significant on the budgetary slack, asymmetry of information also give positive effect and significant on the budgetary slack and budget emphasis give positive effect and significant on the budgetary slack.